Spatial temporal dynamics and influential factors of habitat quality in China's Southern Longji rice terrace ecosystem - Cao Hongli (E3S Web of Conferences)
Rice terrace ecosystems (RTEs) offer a wealth of ecosystem services vital to human well-being. Regrettably, the recent period has witnessed a growing trend of abandonment and habitat degradation within RTEs. This study focuses on the Longji Terraces in Guilin, China, using remote sensing data from 1985–2020 to assess habitat quality (HQ) and its spatial-temporal dynamics. Furthermore, the driving factors of HQ is explored through ordinary least squares (OLS) and geographically weighted regression (GWR) models. The research reveals that forested areas are crucial for HQ, with an overall high average HQ, but significant degradation in certain areas. The growth of the tourism industry and the arrangement of the landscape are recognized as the key drivers of RTE-HQ (average annual R2 = 0.75). The findings provide a scientific basis for the conservation and sustainable use of global rice terraces.